Entre les Pays-d'en-Haut et Montréal: le lieu-dit Lachine - Vaillancourt, Pascale (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal)

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
Keywords: Lachine (canal)

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Les paysages urbains historiques des canaux de Lachine et de Chambly: une démarche exploratoire. - Gelly, Alain; Paradis, Mathieu (Paysages du mouvement/paysages en mouvements: Trajectoires, perspectives et panoramas, 2021)
Keywords: Lachine (canal)

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Keywords: Lachine (canal); Paysages

Aviron Lachine Rowing. 1863-2013: A History - Cabana, Richard (Richard Cabana, 2015)
Keywords: Clubs

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

Évaluation du patrimoine urbain: arrondissement de Lachine - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Lachine; Patrimoine

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

L'axe du canal de Lachine et les quartiers du Sud-Ouest. Grandeur et misère du berceau de l'industrialisation du pays? - Poitras, Claire (Montréal : la cité des cités, 2017)
Keywords: Arrondissements; Côte-Saint-Paul; Griffintown; Groupes populaires; Lachine (canal); Le Sud-Ouest (arrondissement); Patrimoine; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Saint-Henri; Ville Émard

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Montréal hanté: la mémoire macabre d'une cité victorienne - Baril, Pierre-Luc (VLB éditeur, 2024)
Keywords: Cimetières; Guibord, Joseph; Lachine (canal); Photographie; Pied-du-Courant; Redpath (musée); Épidémies

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

L'économie montréalaise au XIXe siècle - Labrecque, Annie-Claude; Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

The Montreal Economy during the Nineteenth Century - Fougères, Dany; Labrecque, Annie-Claude (Montreal: The History of A North American City, 2018)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime